Prevalence of risk factors in cardiovascular diseases in selected population of the Czech Republic - Pavlík, Vladimír; Fajfrová, Jana; Šafka, Václav; Pravdová, Lucie; Urban, Miroslav; Krutišová, Pavla; Tuček, Milan (Central European journal of public health, 2018)
OBJECTIVES: The aim of the study is to describe current prevalence of selected risk factors in the Czech general population in a particular region and to compare the data with recently published results in the selected population of Czech soldiers. The work also deals with the advantages and disadvantages of methods determining overweight and obesity. METHODS: Within medical preventive examinations the data of 1,051 individuals (482 men, 569 women) were obtained. In this group anthropometric parameters such as height, body weight, Body Mass Index (BMI), and waist circumference were monitored. From biochemical parameters the following values were monitored: glycaemia, uric acid, total cholesterol, LDL-cholesterol, HDL-cholesterol, and triglycerides. Demographic data such as age, gender and achieved education were processed. RESULTS: Average BMI values in men were in the overweight range. Monitored average BMI values in women were up to standards. Monitored anthropometric parameters significantly increased with the age of examined individuals. The highest values of BMI and waist circumference were found in the over-50 age group. Selected biochemical parameters also increased with the age of examined individuals. Education did not have significant influence on the values of selected parameters. A statistically significant positive correlation was found between the values of BMI and waist circumference. The correlation coefficient in men was r = 0.804, p < 0.001, and in women r = 0.858, p < 0.001. CONCLUSION: The work confirmed differences in anthropometric parameters between the civilian and military Czech male population due to a higher muscle mass percentage in the military population. The work also confirmed the significance of further anthropometric methods in diagnostics of overweight and obesity. The number of individuals with anthropometric and biochemical parameters out of the physiological range is increasing in the over-50 age category.
Keywords: dospělí; Female; Overweight; Anthropometry; Prevalence; biologické markery; Biomarkers; Adult; ženské pohlaví; obvod pasu; overweight; lipidy; Obesity; lidé; Blood Glucose; Lipids; antropometrie; Waist Circumference; Risk Factors; prevalence; obezita; Male; Cardiovascular Diseases; Czech Republic; nadváha; index tělesné hmotnosti; rizikové faktory; kardiovaskulární nemoci; Česká republika; lidé středního věku; mužské pohlaví; cardiovascular diseases; Body Mass Index; obesity; krevní glukóza; Demography; Middle Aged; preventive measures; anthropometry; demografie; Humans